Properties of Sodium Alginate–Polyvinyl Alcohol Hydrogels Irradiated By Gamma Ray For Wound Dressing Materials - Thamrin Wikanta; Erizal Erizal (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2013)
A copolymer of sodium alginate (SA)–polyvinyl alcohol (PVA) was synthesized by gamma irradiation  to  make  a  hydrogel  and  study  on its properties has been carried out. A  series of 0.5% -2.0% (w/v) of SA solution and 10% (w/v) of PVA solution were prepared in separate tubes. Each of the SA solution was mixed with PVA solution, then it was irradiated with gamma ray at the doses of 30 kGy, 40 kGy, and 50 kGy (dose rate of 10 kGy/hour), respectively. The properties of hydrogels were evaluated comprising of the physical performance, gel fraction, swelling ratio, water evaporation, and pH. The results showed that increase of irradiation dose can increase the gel fraction, but  increase of SA concentration can decrease the gel fraction. SA concentration of 1-2% with gamma ray irradiation dose of 30 kGy was a suitable condition to produce a good hydrogel with properties as follow, gel fraction of 75.83%-78.70%, swelling ratio of 69.12-80.14 g/g, and maximum water evaporated of 54.21-76.41%, the pH value ranged 5.60-5.65. The hydrogels produced are suitable to be used for  wound dressing, especially for wet wounds, and can be applied for two days.